Interfacial Analysis of Surface-Coated LiMn2O4 Epitaxial Thin Film Electrode for Lithium Batteries. Issue 13 (1st January 2015) - Suzuki, Kota; Hirayama, Masaaki; Kim, KyungSu; Taminato, Sou; Tamura, Kazuhisa; Son, Jin-Young; Mizuki, Jun'ichiro; Kanno, Ryoji
Abstract : The effects of surface coatings on LiMn2 O4 were investigated using LiMn2 O4 epitaxial thin films with a thickness of 30 nm. Bare and surface-coated LiMn2 O4 epitaxial thin films were synthesized on SrTiO3 (111) substrates using a pulsed laser deposition method. The surface coating, which was formed using the solid electrolyte Li3 PO4 and had a thickness of 3 nm, improved the reversibility of the electrochemical reactions undergone by the LiMn2 O4 epitaxial thin films. The modified surface structure provided a stable field for reversible reactions at the electrode surface, resulting in superior battery performance. The changes induced in the surface structure were maintained during battery operation; in contrast, the bare LiMn2 O4 thin film exhibited structural degradation and Mn dissolution. The structural changes induced in the coated electrode and the increase in its surface stability were intrinsic effects of the Li3 PO4 coating and improved the electrochemical performance of the LiMn2 O4 thin-film electrode.